Anticonvulsant effect of lercanidipine against pentylenetetrazole induced kindling in mice - Selvaraj, Nitya; Kameswari, Deepa; Gandhi, Ramya; Raja Mohamad, Meher Ali (International Journal of Basic & Clinical Pharmacology, 2017)
Background: Emerging evidence has demonstrated the role of high-voltage -sensitive activated dihydropyridine (L-type, CaV1.x) channels in the development of epilepsy. Based on that we hypothesized that lercanidipine, a dihydropyridine calcium channel blocker, would protect against Pentylenetetrazole (PTZ) induced kindling in mice model of epilepsy. Methods: Kindling was induced in Swiss albino mice with PTZ in subconvulsive dose (30 mg/kg i.p.) thrice a week for nine weeks and the effect was scored using ‘4 point scoring system’. Rechallenging on the 3rd and 10th day with the same dose of PTZ was carried out after the last chronic dose. Results: The data of the present study demonstrated that pretreatment with lercanidipine (½ h before PTZ, in doses of 1 and 3 mg/kg i.p. daily) alone and in combination with diazepam (2mg/kg i.p.) had decreased the incidence and severity of seizure as well as prolonged the onset of kindling in a dose-dependent manner (p <0.05). On rechallenging, lercanidipine resulted in reduction of seizure score (p <0.05) and increased the seizure latency. Conclusions: The present study suggested that lercanidipine offered neuroprotection against PTZ induced kindling in mice.